2017
DOI: 10.1039/c7cc00781g
|View full text |Cite
|
Sign up to set email alerts
|

Oxahelicene NHC ligands in the asymmetric synthesis of nonracemic helicenes

Abstract: A straightforward approach to enantiopure 2H-pyran-modified amino[5]helicenes and amino[6]helicenes was developed. They were converted to 1,3-disubstituted imidazolium salts and used as NHC ligand precursors in the Ni-catalysed enantioselective [2+2+2] cycloisomerisation of aromatic triynes to obtain the model helicene derivatives in up to 86% ee.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 35 publications
0
47
0
Order By: Relevance
“…For these reasons, we have been recently investigating the development of molecular architectures associating helicenes, NHCs, and organometallic chemistry, in order to develop a new family of chiral complexes, namely, organometallic NHC‐helicene complexes (see Figure , A ‐ C ) . This strategy enabled us to create novel chiral molecular materials with unprecedented photophysical properties and potential applications in enantioselective organometallic catalysis . In this article, we present novel [4, 6]helicenic imidazolium salts ( 4a , b ) and their corresponding helicenic NHC ligands mono‐coordinated to iridium(I) ( 1a , b ) and rhodium(I) ( 1′a ) complexes.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, we have been recently investigating the development of molecular architectures associating helicenes, NHCs, and organometallic chemistry, in order to develop a new family of chiral complexes, namely, organometallic NHC‐helicene complexes (see Figure , A ‐ C ) . This strategy enabled us to create novel chiral molecular materials with unprecedented photophysical properties and potential applications in enantioselective organometallic catalysis . In this article, we present novel [4, 6]helicenic imidazolium salts ( 4a , b ) and their corresponding helicenic NHC ligands mono‐coordinated to iridium(I) ( 1a , b ) and rhodium(I) ( 1′a ) complexes.…”
Section: Introductionmentioning
confidence: 99%
“…[1,2] In most cases described so far,N HC-ligands have been chirally modified by introducing centers of chirality, either in the Nsubstituent or in the NHC-backbone (Figure 1). [24] This strategy has in the meantime been successfully applied to the synthesis of enantiopure aminohelicenes, [25,26] which we in turn expect to open the door to NHC ligands with helically chiral N-substituents and transitionmetal catalysts derivedt hereof. It has, for instance, been demonstrated that the reactivity of Ru-metathesis catalysts with unsaturated NHC ligands can be improved by increasing the s-donor capacity of the ligand through introduction of donor substituents in the backbone.…”
mentioning
confidence: 99%
“…[19,21] Helical chirality has so far been unexplored in asymmetric transition-metalc atalysis as as tereoinformation-inducing element. [24] This strategy has in the meantime been successfully applied to the synthesis of enantiopure aminohelicenes, [25,26] which we in turn expect to open the door to NHC ligands with helically chiral N-substituents and transitionmetal catalysts derivedt hereof. [24] This strategy has in the meantime been successfully applied to the synthesis of enantiopure aminohelicenes, [25,26] which we in turn expect to open the door to NHC ligands with helically chiral N-substituents and transitionmetal catalysts derivedt hereof.…”
mentioning
confidence: 99%
“…Helicenes are polycyclic molecules composed of ortho-fused aromatic rings that confer an inherently chiral helical shape to their structures. [1][2][3][4] Owing to their uniques tructural, electronic and chiroptical properties, these compounds are the focus of considerable attention in variousf ields of research, [3][4][5] notably for their potential utility in asymmetricc atalysis, [6][7][8][9][10] molecular recognition, [11][12][13][14][15] supramolecular chemistry, [16][17][18] molecular machines design, [19][20][21][22][23] liquid crystal technology, [24][25][26][27] organic (opto)electronics, [28][29][30][31][32] as well as new materials. [33][34][35][36] Several of these applications necessitate access to optically pure helicenes.…”
Section: Introductionmentioning
confidence: 99%
“…[33][34][35][36] Several of these applications necessitate access to optically pure helicenes. [2][3][4] Although af ew asymmetric synthesis approaches have relied on the use of chiral reagents or catalysts, [10,[37][38][39][40][41][42][43][44][45] most of the others were based on substrate controlt hrough the installationo fc hiral moietieso ntom olecular scaffolds prior to their annulation into helicenic systems. [46][47][48][49][50][51][52][53][54][55][56][57][58][59] However,f ully optically pure materials, which are of paramount importance for anya pplication, are rarely obtained, [45][46][47][48][49][50] and diastereoenriched mixtures generated with the help of chiral auxiliaries still need to be separated by conventional chromatography.…”
Section: Introductionmentioning
confidence: 99%